Antioxidant interaction of α-tocopherol, γ-oryzanol and phytosterol in rice bran oil. (1st May 2021) - Liu, Ruru; Xu, Ying; Chang, Ming; Tang, Lin; Lu, Mengyao; Liu, Ruijie; Jin, Qingzhe; Wang, Xingguo
Highlights: Concentration of binary mixtures affected the total antioxidant capacity. Ratio of binary mixtures affected the type or degree of antioxidant interaction. Inhibition of phytosterol on α-tocopherol regeneration leads to antagonism. Synergism of γ-oryzanol and phytosterol is related to the hydrogen bond. Abstract: In this study, purified rice bran oil (RBO) was used as a lipid matrix model to study the individual and binary antioxidant capacity of the minor constituents (α-tocopherol, γ-oryzanol and phytosterol) added at different concentrations and ratios. The results revealed that concentration influenced on the oxidation stability and scavenging capacity, while ratio mainly affected the type of interaction or the degree of synergism or antagonism. It was important to notice that the antioxidant capacity of α-tocopherol would decrease under high concentration. Besides, the inhibition of phytosterol on α-tocopherol and the formation of hydrogen bond between γ-oryzanol and phytosterol were speculated by the interactions of these minor constituents. This work helps to select efficient combinations for stabilizing the anti-oxidation of nutrient enriched RBO or provide suggestions for moderate retain of minor constituents in RBO.